Effect of Round Robin Instructional Strategy on Pupils’ Academic Achievement in Mathematics - Obafemi, Kayode Ezecheal; Yahaya, Olarewaju; Yakubu, Francis Moodu; Obafemi, Taiye Olayinka (Universitas Pendidikan Indonesia (UPI), 2024)
The study examined the effect of a round-robin instructional strategy on pupils’ academic performance in Mathematics. The study adopted a quasi-experimental research design. Two public primary schools were randomly selected to participate in the study. One validated and reliably tested research instrument titled ‘Mathematics Performance Test’ (MPT) was used. The reliability index of MPT was determined using Pearson Product Moment Correlation (PPMC). Two research hypotheses were formulated and tested with Analysis of Covariance (ANCOVA). The findings of the study revealed that treatment had a significant effect on pupils’ academic achievement in mathematics. However, the interaction of treatment and gender did not have any significant effect on pupils’ academic achievement. Based on the findings, it was concluded that round round-robin instructional strategy can improve the academic achievement of pupils. Based on the conclusion, it was recommended that teachers should be trained on the use of the round-robin instructional strategy.